Study on Ectoparasites of Free-Ranging Domestic Cats (Felidae; Felis catus) and Introducing Trichodectes canis as a New Record Louse in Tehran Urban Parks, Iran - Amrollah Azarm; Abedin Saghafipour; Saeideh Yousefi; Fatemeh Shahidi; Ali Reza Zahraei-Ramazani (Psyche: A Journal of Entomology)
Free-ranging domestic cats (Felidae, Felis catus) can potentially play host to some life-threatening zoonotic pathogens including ectoparasites such as fleas, ticks, and lice. These ectoparasites are capable of transmitting zoonotic disease. Cats (Felis catus) were captured using baited cage traps with raw red meat from five parks in central areas of Tehran, Iran, in the summer of 2018. The collected cats were moved to the laboratory, and their ectoparasites were removed from their skin by forceps and combing for five minutes for each cat. Ectoparasites were stored in 70% ethanol and later mounted for identification of species, using species identification keys. Forty-one cats were collected from these study areas. Among all captured cats, 26 specimens (63.41%) were infected with 83 ectoparasites and the average infection rate was 3.19 in cats. Six arthropod species were identified, including four fleas (89.16%), one louse (8.43%), and one tick (2.41%). The four flea species included Ctenocephalides canis (39.76%), Ctenocephalides felis (18.07%), Xenopsylla nubica (16.87%), and Pulex irritans (14.46%). The one louse species was Trichodectes canis (8.43%), and the one tick species recovered was identified as Hyalomma spp. (2.41%). Based on the findings, Ctenocephalides canis was the most common ectoparasite species (39.76%). Fleas were the most prevalent ectoparasites on Felis catus cats, with the highest prevalence, observed for Ctenocephalides canis. Due to the large and growing population of cats and the high risk of transmission of common diseases between humans and cats, as well as the high contact and communication of people with cats, we were encouraged to study the ectoparasites of cats in five important parks in the city of Tehran.